How anthropogenic forest fires may have impacted earth's climate over 10,000 years ago. (Research'eu results magazine)
Recently paleoclimatologist William Ruddiman suggested that humans may have had a significant impact on the Earth's climate already thousands of years ago- through carbon and methane emissions originating from biomass burning and deforestation associated with early agriculture. The early human impact project set out to verify this hypothesis.